First‐in‐man observation of Talaromyces marneffei‐transmission by organ transplantation. Issue 3 (30th September 2016) - Hermans, Frederik; Ombelet, Sien; Degezelle, Karlien; Testelmans, Dries; Van Raemdonck, Dirk E.; Verleden, Geert M.; Verbeken, Eric K.; Van Bleyenbergh, Pascal; Lagrou, Katrien; Vos, Robin
Summary: A lung transplant recipient was diagnosed with penicilliosis due to Talaromyces marneffei, a fungus endemic in South‐East Asia, which was acquired by donor transmission. This first case of Talaromyces marneffei‐ transmission by transplantation underscores that current globalisation of travelling necessitates increased vigilance for transmission of unusual pathogens in organ recipients.